Refugees in Malaysia: a study of the rights of children and women refugees / Che Rohana Ismail, Nor Rosmardhati Othman and Zati Farahiyah A. Halim - Ismail, Che Rohana; Othman, Nor Rosmardhati; A. Halim, Zati Farahiyah (2008)
Generally, the word 'refugee' is used to describe a person who is forced to flee his or her home for any reason for which the individual is not responsible, be it persecution, public disorder, civil war, famine, earthquake or environmental degradation.1 Under the Refugee Convention 1951, the term 'refugee1 is defined as 'any persons who, owing to a well founded fear of being persecuted for reasons of race, religion, nationality, membership of a particular social group or political opinion, is outside the country of his nationality and is unable or, owing to such fear, is unwilling to avail himself of the protection of that country. In other words, a 'refugee' is a person who is forced to leave home for specified reasons and who is outside the country of his or her origin and does not have its protection. Persons who are compelled to move but do not cross international borders are classifying as 'internally displaced person.